Anthracyclines/trastuzumab: new aspects of cardiotoxicity and molecular mechanisms - Rochette, Luc; Guenancia, Charles; Gudjoncik, Aurélie; Hachet, Olivier; Zeller, Marianne; Cottin, Yves; Vergely, Catherine (Trends in pharmacological sciences (Regular ed.), 2015)
•Anthracyclines and trastuzumab are effective chemotherapies that can cause cardiotoxicity.•Cardiotoxicity is due to a combination of ‘on-target’ and ‘off-target’ effects.•Neuregulin-1 in the microvascular endothelium is involved in cardiotoxicity.•ErbB2 could be a potential target for anticancer therapy.•Heme oxygenase-1 inhibition may be a strategy to enhance the response to chemotherapy.•Notch-1 is a novel target in trastuzumab-resistant breast cancer. Anticancer drugs continue to cause significant reductions in left ventricular ejection fraction resulting in congestive heart failure. The best-known cardiotoxic agents are anthracyclines (ANTHs) such as doxorubicin (DOX). For several decades cardiotoxicity was almost exclusively associated with ANTHs, for which cumulative dose-related cardiac damage was the use-limiting step. Human epidermal growth factor (EGF) receptor 2 (HER2; ErbB2) has been identified as an important target for breast cancer. Trastuzumab (TRZ), a humanized anti-HER2 monoclonal antibody, is currently recommended as first-line treatment for patients with metastatic HER2+ tumors. The use of TRZ may be limited by the development of drug intolerance, such as cardiac dysfunction. Cardiotoxicity has been attributed to free-iron-based, radical-induced oxidative stress. Many approaches have been promoted to minimize these serious side effects, but they are still clinically problematic. A new approach to personalized medicine for cancer that involves molecular screening for clinically relevant genomic alterations and genotype-targeted treatments is emerging.